2010
DOI: 10.1523/jneurosci.3366-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Induced GABA Potentiation after Chronic Morphine Attenuates the Rewarding Effects of Opioids in the Ventral Tegmental Area

Abstract: Gamma-aminobutyric acid (GABA) transmission in the ventral tegmental area (VTA) is critical for fine tuning the activity of dopamine neurons in response to opioids. However, the precise mechanism by which GABA input shapes opioid reward is poorly understood. One day after chronic morphine treatment, we observed a reduction of conditioned place preference (CPP) for low doses of the opioid [D-Ala2, N-MePhe4, Gly5-ol]-enkephalin (DAMGO) and a switch in the functional effects of mu-opioid receptor modulation of GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 30 publications
8
48
2
Order By: Relevance
“…This suggests that the changes in MOR constitutive activity are not a direct response to the chronic administration of morphine itself, but become pronounced later in the withdrawal period. We also observed that the effect of the MOR agonist DAMGO was diminished during morphine withdrawal, as has been reported previously (Madhavan et al, 2010b). This suggests a withdrawal-induced shift toward more constitutively active MORs, allowing for less additional agonist-induced activation.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that the changes in MOR constitutive activity are not a direct response to the chronic administration of morphine itself, but become pronounced later in the withdrawal period. We also observed that the effect of the MOR agonist DAMGO was diminished during morphine withdrawal, as has been reported previously (Madhavan et al, 2010b). This suggests a withdrawal-induced shift toward more constitutively active MORs, allowing for less additional agonist-induced activation.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously shown the facilitating internalization and recycling (not degradation) of the MOR in response to morphine can prevent or delay many of the compensatory homeostatic adaptations that contribute to tolerance and dependence to moderate long-term doses of morphine (Finn and Whistler, 2001;He et al, 2002;He and Whistler, 2005;Kim et al, 2008;Madhavan et al, 2010). Thus, the data reported here, together with these previous results, show that receptor internalization has dramatically different effects on the development of analgesic tolerance and dependence, depending on the trafficking of the targeted receptor.…”
Section: Morphine-induced Down-regulation Of Dmor 639supporting
confidence: 76%
“…One key homeostatic adaptation that contributes to morphine tolerance in WT mice is superactivation of adenylyl cyclase signaling (for review, see Nestler, 2004;Berger and Whistler, 2010). The importance of this adaptation not only to second messenger signaling but also to synaptic adaptations and behavioral withdrawal was recently demonstrated in vivo (Madhavan et al, 2010). Superactivation, in turn, may promote additional and diverse changes in gene and protein expression, all of which play a role in the behavioral manifestation of morphine tolerance and dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GABA receptors are found distributed across both VTA GABA and dopamine cell populations and, consequently, have been proposed to play a crucial role in dopaminergic cell signaling and motivational processes in general (McBride et al 1999;Laviolette and van der Kooy 2001;Macey et al 2001;Walker and Ettenberg 2005;Madhavan et al 2010). For example, both GABA A receptor agonists and antagonists have been reported to produce positive reinforcing properties when microinjected into the VTA (Ikemoto et al 1997(Ikemoto et al , 1998Laviolette and van der Kooy 2001).…”
Section: Vta Gaba Receptorsmentioning
confidence: 99%